Effect of Phosphate Fertilizer and Arbuscular Mycorrhizal Fungi on The Nutrient, Phosphateuptake and in Vitro Digestibility of Alfalfa - Bambang Suwignyo; Bela Putra; Nafiatul Umami; Cahyo Wulandari; Ristianto Utomo (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
This study aimed to determine the effect of arbuscular mycorrhizal fungi (AMF) and phosphate (P) fertilizer on the nutrient content, phosphate uptake and in vitro digestibility of alfalfa (Medicago sativa L.).The research was conducted at green house of Forage and Pastures Science Laboratory, Faculty of Animal Science Universitas Gadjah Mada. The experiment was arranged in Completely Randomized Design using 3x4 factorial patterns with four replications. The first factor was dosage of phosphate fertilizer SP 36 (0, 60, and 120 kg/ha). Second factor was the dosage of AMF (0, 0.8, 1.6, and 2.4kg/ha). The variable measured was nutrient contents (crude protein, dry matter, and organic matter), total P uptake and dry matter and organic matter in vitro digestibility. The results showed that the interaction of AMF and P fertilizer had no significant effect on crude protein and total P uptake, but highly significant effect on the parameters of dry matter, organic matter and dry matter and organic matter in vitro digestibility.